2019
DOI: 10.1002/cbin.11193
|View full text |Cite
|
Sign up to set email alerts
|

Survival of glioblastoma cells in response to endogenous and exogenous oxidative challenges: possible implication of NMDA receptor‐mediated regulation of redox homeostasis

Abstract: Cancer cells are highly metabolically active and produce high levels of reactive oxygen species (ROS). Drug resistance in cancer cells is closely related to their redox status. The role of ROS and its impact on cancer cell survival seems far from elucidation. The mechanisms through which glioblastoma cells overcome aberrant ROS and oxidative stress in a milieu of hypermetabolic state is still elusive. We hypothesize that the formidable growth potential of glioma cells is through manipulation of tumor microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…ROS can cause oxidation of DNA, proteins and lipids, as well as damage to cellular organelles, which ultimately leads to tumorigenesis when the damaged cells accumulate to a certain level (Hayes et al, 2020;Kuo et al, 2022). In our study, we found that H 2 O 2 -induced oxidative stress inhibited proliferation, migration and invasion of U251 cells and promoted cell apoptosis, which was consistent with the results of Dalavaikodihalli et al (2019). NRF1, a redox-sensitive transcription factor, is vital for maintaining healthy redox homeostasis (Yuan et al, 2018;Zhang et al, 2020).…”
Section: Knockdown Of Nor1 Could Alleviate the Antioxidative Stress E...supporting
confidence: 90%
“…ROS can cause oxidation of DNA, proteins and lipids, as well as damage to cellular organelles, which ultimately leads to tumorigenesis when the damaged cells accumulate to a certain level (Hayes et al, 2020;Kuo et al, 2022). In our study, we found that H 2 O 2 -induced oxidative stress inhibited proliferation, migration and invasion of U251 cells and promoted cell apoptosis, which was consistent with the results of Dalavaikodihalli et al (2019). NRF1, a redox-sensitive transcription factor, is vital for maintaining healthy redox homeostasis (Yuan et al, 2018;Zhang et al, 2020).…”
Section: Knockdown Of Nor1 Could Alleviate the Antioxidative Stress E...supporting
confidence: 90%
“…Zhu et al ( 2018 ) demonstrated that TMZ-resistant glioma cells have higher levels of glutathione reductase (GR) and GSH than TMZ-sensitive cells. Dalavaikodihalli Nanjaiah et al ( 2019 ) showed that GSH, GR, and catalase were all up up-regulated through the glutamate-mediated activation of N-methyl-D-aspartate receptor. The expression of the amino acid antiporter that mediates the exchange of extracellular cysteine and intracellular glutamate across the plasma membrane, the system xc − , was found to be elevated in GBM cell lines, increase GSH production, mitochondrial biogenesis, oxidative phosphorylation, and ATP generation (Polewski et al, 2016 ), and conferred resistance to OS while decreasing sensitivity to TMZ.…”
Section: The Pathways Of Resistance To Radio- and Chemotherapy And Prmentioning
confidence: 99%
“…Contrary to the expected results, our study showed that curzerene treatment can reduce the level of intracellular reduced GSH, which may be due to the upregulation of other intracellular oxidative stress products, such as H 2 O 2 , the consumption of GSH by the glutathione peroxidase pathway, or the direct inhibition of intracellular GSH by downregulation of GSTA4. These results further suggest that curzerene may regulate the apoptosis of glioma by changing the redox level of cells 34–36 . At the same time, the combination of curzerene and chemotherapy drugs may improve the drug sensitivity of tumor and promote the sensitivity of drug‐resistant glioma to chemotherapy drugs 37,38 …”
Section: Discussionmentioning
confidence: 76%
“…These results further suggest that curzerene may regulate the apoptosis of glioma by changing the redox level of cells. 34 , 35 , 36 At the same time, the combination of curzerene and chemotherapy drugs may improve the drug sensitivity of tumor and promote the sensitivity of drug‐resistant glioma to chemotherapy drugs. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%